Moyamoya disease: A case report with typical magnetic resonance imaging findings (Indian Journal of Case Reports, 2018)
Moyamoya disease is an idiopathic non-progressive, non-atherosclerotic, and non-inflammatory vasculo-occlusive disease commonly affecting the supraclinoid internal carotid artery with resultant secondary changes which may include infarcts, ischemia, and multiple collaterals within the brain. The term Moyamoya disease is usually reserved for the idiopathic and rarely familial condition where etiology is not known, whereas the term Moyamoya syndrome is reserved for those conditions where etiology is known. Here, we present the case report of a Moyamoya disease and magnetic resonance imaging (MRI) findings with the review of the MRI features.